Smoke gets in your eyes : and other lessons from the crematory - Doughty, Caitlin (W. W. Norton & Company, 2014)
The blogger behind the popular Web series Ask a Mortician describes her experiences working at a crematory, including how she sometimes got ashes on her clothes and how she cared for bodies of all shapes and sizes.